Determinants of low bone mineral density in children with epilepsy. (January 2018) - Fong, Choong Yi; Kong, Ann Nie; Noordin, Mazidah; Poh, Bee Koon; Ong, Lai Choo; Ng, Ching Ching
Abstract: Introduction: Children with epilepsy on long-term antiepileptic drugs (AEDs) are at risk of low bone mineral density (BMD). The aims of our study were to evaluate the prevalence and determinants of low BMD among Malaysian children with epilepsy. Method: Cross-sectional study of ambulant children with epilepsy on long-term AEDs for >1 year seen in a tertiary hospital in Malaysia from 2014 to 2015. Detailed assessment of anthropometric measurements; environmental lifestyle risk factors; serum vitamin D, calcium and parathyroid hormone levels; genotyping of single nucleotide polymorphisms of genes in vitamin D and calcium metabolism; and lumbar spine BMD were obtained. Low BMD was defined as BMD Z-score ≤ −2.0 SD. Results: Eighty-seven children with mean age of 11.9 years (56 males) participated in the study. The prevalence of low lumbar BMD was 21.8% (19 patients). Multivariate logistic regression analysis identified polytherapy >2 AEDs (OR: 7.86; 95% CI 1.03–59.96), small frame size with wrist breadth of <15th centile (OR 14.73; 95% CI 2.21–98.40), and body mass index Z-score < −2.0 (OR 8.73, 95% CI 1.17–65.19) as significant risk factors for low BMD. Conclusion: One-fifth of Malaysian children with epilepsy on long-term AEDs had low BMD. Targeted BMD should be performed for those who are on >2 AEDs, underweight or with small frame size as they are at higher risk of having low BMD. Highlights: Low bone mineral density is prevalent among Malaysian children with epilepsy. Children who are on AED polytherapy, small frame size or underweight BMI are more likely to have low lumbar BMD. In children with epilepsy, targeted BMD assessment among those at higher risk of low BMD need to be provided.